Non-contrast enhanced functional lung MRI in children: systematic review - Streibel, Carmen; Bauman, Grzegorz; Bieri, Oliver; Pusterla, Orso; Stranzinger, Enno; Curdy, Marion; Latzin, Philipp; Kieninger, Elisabeth (Frontiers in Pediatrics, 2025)
ObjectivesMagnetic resonance imaging (MRI) of the lung is well suited for repeated measurements especially in children due to the absence of ionizing radiation. Furthermore, non-contrast-enhanced (NCE) functional MRI techniques provide localized functional information on ventilation and perfusion without specialized set-ups (e.g., hyperpolarized gases) using standard clinical MRI systems. Current NCE-MRI techniques in the pediatric setting are matrix-pencil decomposition (MP)-MRI, phase-resolved functional lung (PREFUL)-MRI, self-gated non-contrast-enhanced functional lung (SENCEFUL)-MRI and Fourier decomposition (FD)-MRI. In this article, we comprehensively discuss these innovative techniques.Study designWe review relevant functional NCE-MRI techniques based on a systematic literature research in MEDLINE, Embase, Cochrane Library, ClinicalTrials.gov and ICTRP. Core concepts were: 1. Aspects regarding lungs 2. MP-, PREFUL-, SENCEFUL and FD-MRI, and 3. children. Consecutively, we included 30 reports.ResultsFunctional NCE-MRI in the pediatric setting has been successfully validated and used in observational studies covering a great variety of lung diseases. In contrast to initial implementation studies additionally reporting on clinical findings, later studies focus primarily on clinical topics. Heterogeneous study designs and examination protocols hamper the direct comparability between the different NCE-MRI techniques in terms of their performance against current functional imaging standards or specific objectives.ConclusionTheir easy applicability makes NCE-MRI techniques highly attractive for widespread clinical use. Following successful implementation studies, still varying test protocols and approaches for calculating outcome values must next be compared and standardized.